"Love" and "death" in the madrigals of Carlo Gesualdo: a study on the development of music and text writing (Per Musi, 2015)
Gesualdo’s compositional writing evolves throughout his six books of madrigals. In the first period, Gesualdo used the most common procedures, such as the contrast between counterpoint and homophony. In the following periods, he began to look for more sophisticated musical elements in order to explore different sounds. Through this process, the composer vigorously emphasized words and, thus, the narrative of the poems, reaching for uncommon harmonic resultants and false melodic relations. The analysis of these words in procedures by Gesualdo reveals his deepening of expressivity and a maturing style.